Genome rearrangements in neurodevelopmental disorders of the central nervous system: origins, genomic mechanisms, functional and clinical consequences. Review article - Kučinskas, V.; Preikšaitienė, E.; Ambrozaitytė, L.; Cimbalistienė, L.; Utkus, A. (Neurologijos seminarai, 2022)
Intellectual disability affects about 1-2% of the general population worldwide, and this is the leading socio-economic problem of the healthcare system. Reasearch into the genetic causes of intellectual disability is challenging because these conditions are genetically heterogeneous with many different genetic alterations resulting in clinically indistinguishable phenotypes. Extensive molecular technologies are being used in research to determine the genetic causes of these conditions. In our research, the detection of chromosomal aberrations by molecular karyotyping and whole exome sequencing capable of uncovering pathogenic variants in any of the human genes were the main technologies used to identify the molecular causes of intellectual disability. Collaboration with foreign scientific institutions for further clinical, molecular and functional investigations of rare causes of intellectual disability has allowed the characterisation of rare known and new syndromes. We believe that new insights into the molecular causes and pathogenesis mechanisms of the intellectual disability may be useful in developing treatment options in the future.
Keywords: genome rearrangements; congenital developmental disorders; ntellectual disability; Alkuraya-Kucinskas syndrome